The Role of The Mythical Imagination in Constructing Popular Patrimony: Some Aspects in The Imouhagh Community - Abdennebi ZENDRI (Turath, 2024)
Many studies have approached popular patrimony through different intellectual orientations and different fields of knowledge. In this research, we aim to present a study of patrimony within the Imouhagh community from the angle of its imaginary component, by studying the case of banquets organised in this region. We have focused on the wedding banquet because of its many customs and traditions and the preparations it requires from the engagement ceremony to the move into the marital home, or what is known among the Imouhagh as alazul.